Alcohol Tolerance in Human Laboratory Studies for Development of Medications to treat Alcohol Use Disorder. (17th January 2020) - Haass-Koffler, Carolina L; Perciballi, Roberta
Abstract: Aims: Human laboratory studies have contributed extensively in the research and development of novel medications to treat alcohol use disorder (AUD). Alcohol tolerance may represent one additional variable that can be utilized to expand the understanding of the AUD wide phenotypic profile and provide support to the medication development process. Tolerance is characterized as an individual's subjective response to alcohol and has been recognized as a predictor of AUD progression. Tolerance can be evaluated both by self-reported response (e.g. assessments) and objective measurements (e.g. motor impairment); as such, it represents an exploitable variable in the field of alcohol research. Methods: This Narrative Review focuses on the use of alcohol tolerance, specifically within alcohol laboratory studies, for medication development. It seeks to identify a research gap and a research opportunity in clinical studies to evaluate biobehavioral responses captured in order to develop medications to treat AUD. Results: Alcohol tolerance may provide additional information on the safety and tolerability of medications to treat AUD, in particular, when novel medications are co-administered with alcohol within the AUD population. Conclusions: As such, alcohol tolerance represents an additional outcome that may be included in randomized clinical trial (RCT) protocols designed for developing AUD pharmacotherapies.